Stimulation of polymorphonuclear leukocyte activity under the influence of low strength electric field - Kavalenka, Alena I.; Yushkevich, Artsemi M.; Kavalenka, Elizaveta A.; Kavalenka, Anton N. (Journal of the Belarusian State University. Physics, 2020)
It is assumed that electrical stimulation can be the most important physical effect providing regulation of the activity of immune cells such as polymorphonuclear leukocytes (PMNL). To study the effect of electrical stimulation on PMNL activity, the experimental setup based on electric signal generator and biochemiluminometer was developed, which allows performing electrostimulation of cells and studying the generation of reactive oxygen species (ROS) in PMNL simultaneously. Impact on the cells was carried out using electrodes immersed in incubation medium connected to electric signal generator. Non-uniform electric field was established, the intensity of which decreased with distance and time that imitated the characteristics of endogenous electric fields in places of inflammation in organism. During stimulation, the field strength was low, up to 1 V/cm. It was found that as a result of electrical stimulation, a change in the functional capabilities of human blood PMNL is observed. The severity of effects depends on the voltage applied to the electrodes and the duration of the observation. The key functional processes in PMNL such as ROS generation and myeloperoxidase enzyme secretion are enhanced in the initial period of electric field influence. A few hours after electrical stimulation, inhibition of PMNL activity and the gradual destruction of cells are observed. The obtained data testify the regulatory role of electrical stimulation in relation to PMNL activity which necessary for the implementation of the bodyʼs immune defense.